MicroRNA-886-3P functions as a tumor suppressor in small cell lung cancer. Issue 12 (2nd December 2018) - Shen, Jie; Zhou, Wei; Bi, Nan; Song, Yong-Mei; Zhang, Fu-Quan; Zhan, Qi-Min; Wang, Lv-Hua
ABSTRACT: Small cell lung cancer (SCLC) is a highly aggressive disease and miRNAs may play an important role in modulating SCLC progression. We have previously screened 924 miRNAs and found that miR-886-3P was negatively associated with SCLC survival. In the current study, we further investigated the role of miR-886-3P mimic in regulating SCLC cell phenotypic alteration in vitro and xenograft tumor formation in vivo . We found that transfection of miR-886-3P mimic significantly inhibited SCLC cell proliferation, migration, and colony formation, and induced mesenchymal-epithelial transition (MET) by suppressing TGF-ß1 synthesis in vitro . Furthermore, intra-tumor injection of miR-886-3P mimic lead to necrosis and suppression of tumor invasion to the surrounding tissue in the subcutaneous xenograft tumor, and intra-vein injection of miR-886-3P mimic suppressed xenograft lung cancer growth in vivo . These findings suggested that miR-886-3P functions as a tumor suppressor in SCLC and thus, it might be a potential therapeutic molecule in the treatment of lung cancer.